A review of literature on the therapeutic use of music with military populations experiencing post-traumatic stress disorder - Thomas, Rachael; F Chichaya, Tongai (Journal of Associated Medical Sciences, 2023)
Background: Post-traumatic stress disorder (PTSD) is frequent among military populations. Symptoms range from physical to behavioural, and emotional difficulties. Loneliness and feeling misunderstood are common among military personnel, particularly veterans. Service members returning from duty often experience a lack of support and this predisposes them to an increased risk for suicide. Music can be therapeutically used with military populations through a range of methods, especially in mental health settings. Participating in music can be a meaningful occupation for many but there is a scarcity of literature on the therapeutic use of music in occupational therapy. Objectives: The purpose of this literature review was to synthesize current qualitative evidence on the perceptions and experiences of the military population who engage in music therapy. Materials and methods: A scoping review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis extension for Scoping Reviews (PRISMA-ScR) checklist guidelines. Varied databases were searched to retrieve qualitative papers on the lived experiences of the therapeutic use of music among people in the military published between January 2012 and December 2022. Following the quality appraisal, data from the included papers were collated in a data abstraction form before being synthesized thematically. Results: Seven studies met the inclusion criteria and were included in this scoping review. Three themes were identified: emotional regulation, engaging with others, and mental health stigma. Therapeutic use of music was found to be beneficial and service members expressed that they have managed to overcome mental health challenges, find new connections, and engage with others. However ethical challenges and the delivery of therapeutic use of music must be carefully monitored. Conclusion: Overall, the therapeutic use of music within military populations with PTSD is perceived to be beneficial and worth continuing with however, careful monitoring during treatments should be a priority to prevent outbursts, relapse, or aggressive behaviours. Combining occupational therapy and music therapy could maximize the benefits of music to people with mental health conditions.